Validation of a noninvasive system for measuring head acceleration for use during boxing competition - Beckwith, J. G.; Chu, J. J.; Greenwald, R. M. (Journal of Applied Biomechanics, 2007)
Although the epidemiology and mechanics of concussion in sports have been investigated for many years, the biomechanical factors that contribute to mild traumatic brain injury remain unclear because of the difficulties in measuring impact events in the field. The purpose of this study was to validate an instrumented boxing headgear (IBH) that can be used to measure impact severity and location during play. The instrumented boxing headgear data were processed to determine linear and rotational acceleration at the head center of gravity, impact location, and impact severity metrics, such as the Head Injury Criterion (HIC) and Gadd Severity Index (GSI). The instrumented boxing headgear was fitted to a Hybrid III (HIII) head form and impacted with a weighted pendulum to characterize accuracy and repeatability. Fifty-six impacts over 3 speeds and 5 locations were used to simulate blows most commonly observed in boxing.A high correlation between the HIII and instrumented boxing headgear was established for peak linear and rotational acceleration (r2= 0.91), HIC (r2 = 0.88), and GSI (r2 = 0.89). Mean location error was 9.7 ± 5.2º. Based on this study, the IBH is a valid system for measuring head acceleration and impact location that can be integrated into training and competition.